2004
DOI: 10.1103/physrevlett.92.214801
|View full text |Cite
|
Sign up to set email alerts
|

Beam-Beam Limit ine+eCircular Colliders

Abstract: Beam-beam effects limit the luminosity of circular colliders. Once the bunch population exceeds a threshold, the luminosity increases at a slower rate. This phenomenon is called the beam-beam limit. Onset of the beam-beam limit has been analyzed with various simulation methods based on the weak-strong and strong-strong models. We have observed that an incoherent phenomenon is mainly concerned in the beam-beam limit. The simulation have shown that equilibrium distributions of the two colliding beams are distort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…We present a typical result, a single-bunch luminosity simulation for Super-KEKB with parameters as given by Ohmi et al [8]. We observe good agreement with the results in Ref.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…We present a typical result, a single-bunch luminosity simulation for Super-KEKB with parameters as given by Ohmi et al [8]. We observe good agreement with the results in Ref.…”
Section: Resultssupporting
confidence: 78%
“…Numerical methods used to determine them have converged on using PIC methods, modeling the collision process as a series of synchro-betatron mappings of test particles in the presence of two-dimensional field distributions (Ref. [8] and references therein). We have developed a code using this principle adapted to high longitudinal resolution, extreme aspect ratios, and the presence of parasitic crossings resulting in multi-bunch effects.…”
Section: The Strong-strong Beam-beam Effect: Nimzovichmentioning
confidence: 99%
“…We have two other simulation methods, which are not treated in this paper. They are strong-strong simulation with a Gaussian approximation and weak-strong simulation with the particle-in-cell (PIC) method [15,16]. In the first method, both beams, which are represented by macroparticles, are approximated by Gaussian distributions turn by turn.…”
Section: A Treatment Of the Crossing Anglementioning
confidence: 99%
“…No serious problems due to the crossing angle have been observed in the range of the vertical beam-beam tune shift parameter ξ y ∼ 0.05. However, the recent beam-beam simulation has suggested that head-on collision will improve ξ y significantly ( ξ y > 0.1) [2]. In order to recover an effective headon collision at KEKB, crab cavities have been installed in both rings (one cavity per ring) and beam operation has been on the way since February 2007.…”
Section: Introductionmentioning
confidence: 99%